Polityka, poetyka i „tragizm istnienia”. Cenzorska recepcja cyklu powieściowego Młyny Boże Kazimierza Truchanowskiego - Mojsak, Kajetan (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The article analyzes the reception of Kazimierz Truchanowski’s novel cycle “The Mills of the God”, published between 1961 and 1967, by the censorship bureau. The analysis offers insight into the interesting process of growing tolerance – and indifference – of the censorship bureau towards this kind of hermetic, non-epic prose: far from the official cultural course, but at the same time not engaging in open conflict with it. Review of cen-sors’ reception of the subsequent parts of Truchanowski’s novel can be seen as a contribution to the history of the socalled “socparnasizm” as well as to the history of the growing pragmatism of the censorship board (and its de-ideologization).